Kaidah-Kaidah Fikih yang Berkaitan Dengan Keyakinan - A, Arlan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to study in depth the fiqh rules related to belief (yaqin) as an important pillar in maintaining the certainty and stability of Islamic law. The main focus is directed on four main principles: al-yaqin la yazulu bi al-shakk, al-original baqa’ ma kana ‘ala ma kan, al-asl baraʾat al-dhimmah, and al-asl fi al-asyya’ al-ibahah. These rules are analyzed in their historical, normative, and contextual dimensions through a literature-study-based qualitative-descriptive approach. Data sources were obtained from classical literature such as the works of al-Suyuthi, al-Syatibi, and al-Ghazali, as well as contemporary literature from thinkers such as Yusuf al-Qaradawi and Jasser Auda, including the contributions of UIN academics Alauddin Makassar. The results of the study show that the rules based on the principle of belief are not only theoretical in nature, but have a high applicative value in the fields of worship, transactions, and judicial law. This principle serves as a mechanism of Shariah safeguarding against doubt, as well as being the foundation for a fair, rational, and contextual reconstruction of Islamic law. This study recommends the strengthening of the integration between qaida yaqin and maqasid al-shari‘ah to answer the challenges of contemporary Islamic law that demand precision as well as legal completeness.